Cytotoxic effect and apoptotic induction of tricyclohexyltin p-methoxycinnamate on HT-29 colorectal cancer cells: Implications for anticancer therapeutics - Abdah Md Akim; Gul-e-Saba Chaudhry; Zeenia; Tan Weay Ken; Yeong Yik Sung; Tengku Sifzizul Tengku Muhammad (Journal of Advanced Pharmaceutical Technology & Research)
Colorectal cancer’s escalating prevalence in Malaysia prompts the exploration of innovative anticancer agents; amidst this backdrop, tricyclohexyltin p-methoxycinnamate emerges as a synthesized organotin complex with unique bioactive properties. Notably, the novelty of this research lies in its groundbreaking investigation into the hitherto unexplored anticancer potential and mode of cell death induced by tricyclohexyltin p-methoxycinnamate on colon cancer (human colorectal adenocarcinoma cell line (HT-29)) cell lines. This study pioneers the assessment of tricyclohexyltin p-methoxycinnamate’s cytotoxic effects through the “(3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide) assay,” revealing a dose- and time-dependent cytotoxicity with IC50 values of 1.2 × 10-6M for 24 h, 1.0 × 10-6M for 48 h, and 5.0 × 10-7M for 72 h. The mode of cell death through “AO/PI” staining alongside cell cycle analysis, highlighting apoptosis as the predominant mode of cell death in the HT-29 cell line, accompanied by substantial cell cycle arrest at the sub-“G0” phase. The tricyclohexyltin p-methoxycinnamate’s shown potential antiproliferative properties, cell cycle arrest, and apoptosis in HT-29 cancer cells. This novel insight into the compound’s mode of action positions it as a promising candidate for future anticancer therapeutics. The study underscores the urgency of investigating innovative approaches amidst the rising colorectal cancer rates, emphasizing the compound’s potential through further in-depth studies and preclinical trials.